2012
DOI: 10.1017/s1049023x1200088x
|View full text |Cite
|
Sign up to set email alerts
|

CPR Skill Retention of First Aid Attendants within the Workplace

Abstract: The results of this study suggest that repetition may be more important than days since last trained for skill and knowledge retention, and methods of "refreshing" skills should be examined. While skills deteriorate rapidly, changing frequency of certification is not necessarily the best way to increase retention of skill and knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 14 publications
3
21
0
Order By: Relevance
“…The length of training and the absence of training refresher courses may have been insufficient to produce larger changes (cf. Anderson, Gaetz, Statz, & Kin, 2012). The quantitative measures may have been insufficiently sensitive to change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The length of training and the absence of training refresher courses may have been insufficient to produce larger changes (cf. Anderson, Gaetz, Statz, & Kin, 2012). The quantitative measures may have been insufficiently sensitive to change.…”
Section: Discussionmentioning
confidence: 99%
“…(Aveyard, Begh, Parsons, & West, 2012;Sagherian, Huedo-Medina, Pellowski, Eaton, & Johnson, 2016;Sullivan, Tetrault, Braithwaite, Turner, & Fiellin, 2011) and similar evidence specifically for resilience (Leppin et al, 2014;Robertson et al, 2015); however, programs that are longer and that are directed toward people with specific problems or issues can be expected to produce larger outcomes. There is also evidence that skills are enhanced when programs involve repeated skill review and ongoing training (Anderson et al, 2012). Future researchers should consider engaging training refreshers to assess for the incremental impact of additional training.…”
Section: Limitationsmentioning
confidence: 99%
“…Furthermore, prior research on first aid and basic life support courses have demonstrated significant skill decay over time. [20][21][22][23] B-Con's effectiveness has yet to be formally evaluated immediately after laypersons are trained or the retention of the knowledge and skills over time.…”
mentioning
confidence: 99%
“…Previous studies suggested that CPR skills declined faster than expected, 25,26 and that a repeated training course can obviously maintain CPR performance for a long time. 22,27 The CPR Guidelines recommend that skill performance should be reinforced more often with an interval of at most 12-24 months to maintain the quality of the rescuer's CPR.…”
Section: Discussionmentioning
confidence: 82%